2020
DOI: 10.1080/13696998.2020.1791889
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of biologic versus non-biologic treatments and the health-related quality of life among a sample of patients with inflammatory bowel disease in a tertiary care center in Saudi Arabia

Abstract: The cost-effectiveness of biologic versus non-biologic treatments and the health-related quality of life among a sample of patients with inflammatory bowel disease in a tertiary care center in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(61 reference statements)
0
5
0
2
Order By: Relevance
“…A study of the literature revealed that prior trials evaluating the efficacy of ADA and IFX in Crohn's patients mainly assessed the medications' clinical efficacy ( 33 38 ). Other studies have investigated the efficacy of biological medications to non-biologic drugs in people with Crohn's disease or IBD ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the literature revealed that prior trials evaluating the efficacy of ADA and IFX in Crohn's patients mainly assessed the medications' clinical efficacy ( 33 38 ). Other studies have investigated the efficacy of biological medications to non-biologic drugs in people with Crohn's disease or IBD ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Almaslami et al 25 AlRuthia et al 26 Almalki et al 27 Al-Senani et al 28 Hersi et al 29 Knott et al 30 Cara et al 31 Alsaqa'aby et al 32 Al-Aidaroos et al 33 Gupta et al 34 Joosub et al 35 Nasef et al 36 25 AlRuthia et al 26 Almalki et al 27 Al-Senani et al 28 Hersi et al 29 Knott et al 30 Cara et al 31 Alsaqa'aby et al 32 Al-Aidaroos et al 33 Gupta et al 34 Joosub et al 35 Nasef et al 36…”
Section: Studymentioning
confidence: 99%
“…Almaslami et al 25 AlRuthia et al 26 Almalki et al 27 Al-Senani et al 28 Hersi et al 29 Knott et al 30 Cara et al 30 Alsaqa'aby et al 32 Al-Aidaroos et al 33 Gupta et al 34 Joosub et al 35 Nasef et al 36 the definition and criteria for choosing the comparator are not clearly stated within the analyses. Estimating costs should include payers' and societal perspectives in the reference case, as described in the second panel.…”
Section: Table 3 Limitation Domain Summary Details Amentioning
confidence: 99%
“…In contrast, the concomitant use of anti-TNF biologics (INF or ADA) with an immunomodulator, such as azathioprine, and proactive therapeutic drug monitoring are associated with lower risk of treatment failure with anti-TNF therapy [ 28 , 29 ]. In Saudi Arabia, the utilization of biologics in general, and anti-TNF, in particular, is believed to be as high as 60% among CD patients [ 30 , 31 ]. However, no study has, so far, compared the rates of treatment failure among IBD patients treated with INF or ADA, which are the most-commonly utilized biologics in Saudi Arabia for IBD treatment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the utilization of biologics in general, and anti-TNF, in particular, is believed to be as high as 60% among CD patients [ 30 , 31 ]. However, no study has, so far, compared the rates of treatment failure among IBD patients treated with INF or ADA, which are the most-commonly utilized biologics in Saudi Arabia for IBD treatment [ 31 ]. Therefore, the aims of this study were to compare the rates and predictors of treatment failure among IBD patients on anti-TNF biologics in Saudi Arabia, as demonstrated by the presence of deep ulcers and a simple endoscopic score (SES–CD) of one or more for CD, and a Mayo score of two or more for UC patients [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%